2020
DOI: 10.1038/s41598-020-77023-z
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of neuropsychiatric symptoms with APOE ε4 and conversion to dementia in MCI patients in a Memory Clinic

Abstract: To date, very few studies have been focused on the impact of the convergence of neuropsychiatric symptoms (NPS) and APOE ε4 on the conversion to dementia in patients with Mild Cognitive Impairment patients (MCI), and none has been based in a clinical setting. The objective of the study is to determine the predictive value of additive and multiplicative interactions of NPS and APOE ε4 status on the prediction of incident dementia among MCI patients monitored in a Memory Clinic. 1512 patients (aged 60 and older)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…In a search of profiles of clustered symptoms that could serve as markers of disease progression in early stages, NPS would act as early clinical manifestations of an emergent process of neurodegeneration ( Gallagher et al, 2017 ). In particular, affective NPS (depression, apathy, anxiety and irritability) were associated with a more rapid progression to AD in older adults with MCI ( Jang et al, 2020 ), and those have also even shown synergic effects with the APOE ε4-allele ( Valero et al, 2020 ). Recently, some attempts have been made to investigate grouped NPS as possible predictors of cognitive decline along the progression of MCI toward dementia ( Palmer et al, 2007 ; Edwards et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a search of profiles of clustered symptoms that could serve as markers of disease progression in early stages, NPS would act as early clinical manifestations of an emergent process of neurodegeneration ( Gallagher et al, 2017 ). In particular, affective NPS (depression, apathy, anxiety and irritability) were associated with a more rapid progression to AD in older adults with MCI ( Jang et al, 2020 ), and those have also even shown synergic effects with the APOE ε4-allele ( Valero et al, 2020 ). Recently, some attempts have been made to investigate grouped NPS as possible predictors of cognitive decline along the progression of MCI toward dementia ( Palmer et al, 2007 ; Edwards et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in MCI have examined such interactions, finding that co‐occurrence of APOE ɛ4 and apathy posed the greatest risk for incident dementia. 29 , 30 While concomitance of the aforementioned risk marker is associated with greater dementia risk, a systematic review and meta‐analysis investigating the relationship between APOE and affective symptoms in MCI and AD dementia found no evidence that APOE ɛ4 carriership is associated with the presence of apathy. 31 The lack of an association may be the result of capturing apathy with more liberal conventional approaches versus the more conservative MBI approach used for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Until present, little was known about the interaction between APOE genotype and NPS in determining risk, especially in NC. Studies in MCI have examined such interactions, finding that co‐occurrence of APOE ɛ4 and apathy posed the greatest risk for incident dementia 29,30 . While concomitance of the aforementioned risk marker is associated with greater dementia risk, a systematic review and meta‐analysis investigating the relationship between APOE and affective symptoms in MCI and AD dementia found no evidence that APOE ɛ4 carriership is associated with the presence of apathy 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Additive interactions were obtained for depression, apathy, anxiety, agitation, appetite, or irritability and positive ε4 carrier status, which significantly increased the risk ratio for dementia. A combination of behavioral status and genetic trait could be considered to identify subjects with MCI most likely to progress to dementia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%